2020
DOI: 10.24959/ophcj.20.200019
|View full text |Cite
|
Sign up to set email alerts
|

The virtual screening application for searching potential antiviral agents to treat COVID-19 disease

Abstract: Використання віртуального скринінгу з метою пошуку потенційних противірусних агентів для лікування коронавірусної хвороби COVID-19 Мета. Надати скорочений огляд літературних даних стосовно будови коронавірусу людини SARS-CoV-2, механізму його репродукції та ролі вірусних протеаз у цьому процесі. За допомогою інструментів комп'ютерного моделювання проаналізувати здатність відомих противірусних агентів та de novo синтезованих сполук зв'язувати та пригнічувати головну протеазу коронавірусу. Результати та їх обгов… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We also generated a tetrad mutant F147L/F149L/F229L/F231L by replacing residues F147, F149, F229, and F231 with Leu. These mutants were made using PyMol software package 16,17 …”
Section: Methodsmentioning
confidence: 99%
“…We also generated a tetrad mutant F147L/F149L/F229L/F231L by replacing residues F147, F149, F229, and F231 with Leu. These mutants were made using PyMol software package 16,17 …”
Section: Methodsmentioning
confidence: 99%
“…ORFs encode these proteins at the 3 ′ -end of genomic RNA. 9,12,28 6. Structural and non-structural proteins of SARS-CoV-2…”
Section: Molecular Architecture Of the Virus Sars-cov-2mentioning
confidence: 99%
“…A critical assessment of docking programs and scoring functions in terms of reproducing crystallographically determined protein/ligand complex structures is available in [93]. Numerous molecular docking studies have been reported in the context of repurposing and discovering potent non-covalent and covalent inhibitors for critical proteases of the virus SARS-CoV-2 [111][112][113][114][115][116][117][118]. Some excellent reviews of this topic are given elsewhere [1,2,7,119].…”
Section: Pharmacophore-based Virtual Screeningmentioning
confidence: 99%